INTENSITY OPTIMUM SAMPLE FOR CUBING OF Tectona grandis L.f. - VENDRUSCOLO, Diogo Guido Streck; GAVA, Fernando Henrique; DRESCHER, Ronaldo; SOUZA, Hudson Santos; CALDEIRA, Gabriel Valadares; SILVA, Raiane Scandiane da (Brazilian Journal of Biometrics, 2016)
This study aimed to evaluate the sampling intensity, about the number of trees to be cubed to fit volumetric equations for young clonal stands of Tectona grandis (teak). The stand was four years old and it was measured in a 10.6 hectare area, under 4×3 m spacing. The database comes from 80 representative tress cubed. To evaluate the reducing effect of sampling intensity, in the quality of model fit, were tested four scenarios, oscillating the number of trees from 50 to 20. The volume model used was Schumacher and Hall, and for each scenario the equations were validated. The validation criteria of estimates were by statistical parameters and graphical analysis of residue. In addition, the observed values were compared with estimated calculating t test for equations. Equations from different scenario presented appropriate goodness-of-fit statistics, and through this research, it can be verified that the Schumacher and Hall fitted model from 30 produce reliable volumetric predictions in individual clonal stands of young teak.